Publisher Correction: The lipid code-dependent phosphoswitch PDK1-D6PK activates PIN-mediated auxin efflux in Arabidopsis - Tan, Shutang; Zhang, Xixi; Kong, Wei; Yang, Xiao-Li; Molnár, Gergely; Vondráková, Zuzana; Filepová, Roberta; Jan Petrášek; Friml, Jiří; Xue, Hong-Wei (Nature plants, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.